Children's moral evaluations of prosocial and self-interested lying in relation to age, ToM, cognitive empathy and culture. Issue 4 (3rd July 2020) - Lim, Jiayuan; Peterson, Candida C.; De Rosnay, Marc; Slaughter, Virginia
ABSTRACT: Moral evaluations of prosocial lies and selfish lies were examined in 156 children aged 6 to 12 years (77 Australian; 79 Singaporean; mean age 9.38 years) along with theory of mind (ToM) and cognitive empathy. The cultures were chosen because while highly similar in many respects they differ in values orientation, Singapore being highly collectivist and Australia highly individualistic. Results showed that ToM and cognitive empathy each displayed significant links with various aspects of moral evaluation in each culture. Furthermore, Singaporean children displayed significantly higher intention sensitivity (a hallmark of theory) than their matched Australian peers. Hierarchical multiple regression analysis for the full sample showed that this developmentally advanced moral thinking was significantly predicted by cognitive empathy and by culture even after other variables (age, ToM, etc.) were statistically controlled. Findings add to growing evidence of interconnections among social cognition, culture and children's solutions to the everyday puzzles of social life, including whether or not to engage in polite dishonesty.